China’s Search for Good Governance
VII, 244 p. 2 illus.
Keywords: Governance has emerged as a central concept and key word in China's governmental and local policy and practice at different levels. This edited collection combines empirical and normative researches as well as theoretical exploration and case studies on the governance theories and practices in China.